2012
DOI: 10.1371/journal.pone.0033284
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide DNA Methylation Indicates Silencing of Tumor Suppressor Genes in Uterine Leiomyoma

Abstract: BackgroundUterine leiomyomas, or fibroids, represent the most common benign tumor of the female reproductive tract. Fibroids become symptomatic in 30% of all women and up to 70% of African American women of reproductive age. Epigenetic dysregulation of individual genes has been demonstrated in leiomyoma cells; however, the in vivo genome-wide distribution of such epigenetic abnormalities remains unknown.Principal FindingsWe characterized and compared genome-wide DNA methylation and mRNA expression profiles in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
84
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(93 citation statements)
references
References 42 publications
3
84
1
5
Order By: Relevance
“…The functional significance of missense mutations to this mediator complex protein and its developmental origins are not currently known. Alternative mechanisms including epigenetic variations, microRNA-mediated posttranscriptional gene regulation, and altered cell signaling have recently gained traction as putative disease initiating events (7)(8)(9)(10)(11)(12). Several recent studies have demonstrated a central role for a dysregulated phosphoinositide 3-kinase-protein kinase B/AKT (PI3K/AKT) pathway leading to the activation of mammalian target of rapamycin (mTOR) in the pathogenesis of leiomyomas (13)(14)(15).…”
mentioning
confidence: 99%
“…The functional significance of missense mutations to this mediator complex protein and its developmental origins are not currently known. Alternative mechanisms including epigenetic variations, microRNA-mediated posttranscriptional gene regulation, and altered cell signaling have recently gained traction as putative disease initiating events (7)(8)(9)(10)(11)(12). Several recent studies have demonstrated a central role for a dysregulated phosphoinositide 3-kinase-protein kinase B/AKT (PI3K/AKT) pathway leading to the activation of mammalian target of rapamycin (mTOR) in the pathogenesis of leiomyomas (13)(14)(15).…”
mentioning
confidence: 99%
“…Ugyanakkor tisztázásra vár, hogy e gének effektorként vagy promoterként vesznek-e részt a myomák keletkezésében, növekedésében [26]. Az epigenetikai mechanizmusok közül különösen a DNS-metiláció megváltozása, illetve a hisztonmodifi kációs folyamatok ját-szanak fontos szerepet a transzkripció szabályozásában.…”
Section: Epigenetikai Mechanizmusok a Leiomyoma Uteri Kialakulásának unclassified
“…Navarro 2012-ben napvilágot látott közleménye ösz-szesen 36 olyan gént említ, amelyeknek hipometiláció révén létrejövő funkció csökkenése/gátlása a myomaszövetben egyértelműen igazolható [26]. E gének közül a KRT19 (keratin 19; 17q21.2), a KLF11 (Kruppel-like factor 11; 2p25), a DLEC1 (deleted in lung and esophageal cancer 1; 3p21.3), a HOXA5 (homebox 5; 7p15.2), illetve a CLDN5 (claudin 5; 22q11.21) érde-mes kiemelésre.…”
Section: Epigenetikai Mechanizmusok a Leiomyoma Uteri Kialakulásának unclassified
See 2 more Smart Citations